Exploring the perception and acceptance of texture-modified foods among the elderly in Selangor, Malaysia. - Faat, Farhan; Mohtar, Muhammad Mustaqim; Nossro, Nurul Huda; Badiuzaman, Ahmad Fauzan; Mohamed Idris, Aida Khalida; Mazlan, Nor Hafizah (Journal of Islamic, Social, Economics and Development, 2025)
As the world population ages, texture-modified foods (TMFs) among elderly people are a topic of growing interest due to the high prevalence of eating difficulties in this population, which may increase their risk to health. However, there is a lack of studies documented regarding this issue, especially from a Malaysian perspective. Hence, this study aims to explore the perception and acceptance of texture-modified foods (TMFs) among elderly people, specifically in Selangor. To achieve the objectives, qualitative research was conducted, and a total of fourteen (14) elderly people were interviewed face-to-face in pairs for data collection. The data were then analysed, and the result shows themes such as Favoured, Understanding, and Insight have emerged to know the perception of texture-modified foods (TMFs) among elderly people. Meanwhile, Enjoyment and Requirements from the elderly were acknowledged in terms of to what extent does texture-modified foods (TMFs) are accepted, as the evidence shows that texture-appropriate and palatable texture-modified foods (TMFs) can significantly improve the elderly’s nutrition intake and quality of life. After all, deeper exploration and investigation must be carried out to discover more effective actions that could be taken to help the well-being of elderly people.